Effects of Corn Cob Biochar and Plant Density on Zinc Uptake and Growth of Vetiver Grass (Chrysopogon zizanioides) in Leachate-Contaminated Landfill Soil - Muhammad Luthfi Fachrezi; Endah Dwi Hastuti; Yulita Nurchayati (UIN Sunan Gunung Djati Bandung, 2026)
Leachate contamination from landfill waste can increase zinc (Zn) concentrations in soil beyond permissible limits. This study evaluated the effects of corn cob biochar and plant density on Zn uptake and growth of vetiver grass (Chrysopogon zizanioides) grown in leachate-contaminated landfill soil. The experiment was arranged in a completely randomized design with a 2 × 2 factorial scheme and three replications. The first factor was biochar application (without biochar and with biochar), and the second factor was plant density (1 plant and 3 plants per planting bag). The results showed that neither biochar nor plant density, nor their interaction, had a significant effect on soil Zn concentration, root bioconcentration factor (BCF), shoot BCF, and translocation factor (TF). Biochar treatment was associated with lower residual soil Zn concentrations (48.33 mg/kg), higher root bioconcentration factor (BCF) (1.21), and lower shoot BCF (0.78) and translocation factor (TF) (0.70) compared to the treatment without biochar. Similarly, higher plant density showed comparable trends, with lower residual soil Zn concentrations (47.92 mg/kg), higher root BCF (1.33), and lower shoot BCF (0.85) and TF (0.85) compared to lower plant density. However, biochar significantly increased root length, while higher plant density significantly increased shoot dry weight, root biomass, leaf number, and tiller number per planting bag, but decreased plant height per planting bag. Fresh shoot weight per planting bag did not differ significantly among treatments. There was an interaction between biochar and low plant density that increased plant height. The absence of an unplanted control limits the interpretation of Zn reduction. Overall, biochar application and higher plant density were associated with improved growth performance of vetiver grass and may contribute to enhanced Zn uptake characteristics under leachate-contaminated conditions.